Long-term effects of intravenous iloprost therapy in patients with bone marrow oedema of the knee joint - Zippelius, T; Matziolis, G; Perka, C; Putzier, M; Strube, P; Röhner, E (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY Bone marrow oedema (BMO) syndrome is a multifactorial condition. Various conservative treatment options include analgesic therapy, immobilisation of the affected joint and/or systemic intravenous iloprost therapy. Many studies have confirmed the positive effect of iloprost therapy, but only after short-term follow-up. The purpose of this study was to show that treatment with iloprost leads to positive long-term functional and radiological outcomes for BMO of the knee. MATERIAL AND METHODS Fifteen patients with BMO of the knee joint, ARCO stage 1-2, were included in this study. Various questionnaires, the Lysholm Score, the SF-36, WOMAC, Knee Society Score, and a visual analogue pain scale (VAS), were evaluated before and after iloprost therapy. All patients underwent MRI for radiological follow-up three months after treatment. RESULTS Significant improvements were found in the Lysholm Score, SF-36, WOMAC and KSS. In 80% of patients, follow-up MRI after three months showed complete regression of the oedema. Three patients received additional surgery after a follow-up period of 33 ± 7 months. CONCLUSIONS Based on the positive results of our study, we recommend treatment with iloprost for BMO of the knee in ARCO stage 1-2 patients. Key words:iloprost, bone marrow oedema, knee joint.
Keywords: Magnetic Resonance Imaging; Drug Monitoring; Pain Measurement; magnetická rezonanční tomografie; Humans; Radiography; lidé středního věku; vazodilatancia; nemoci kostní dřeně; monitorování léčiv; radiografie; Female; iloprost; Edema; výsledek terapie; lidé; intravenózní podání; Bone Marrow Diseases; Germany; Německo; Knee Joint; ženské pohlaví; Male; edém; Middle Aged; Treatment Outcome; Iloprost; Vasodilator Agents; mužské pohlaví; Administration, Intravenous; měření bolesti; kolenní kloub